Competência oral-enunciativa em língua estrangeira (inglês): fronteiras e limites - Castro, Maria de Fátima Fonseca Guilherme de (2008)
This thesis was developed in an inter/transdisciplinary approach that involves Applied Linguistics (AL), French Discourse Analysis (DA) and Dialogical Discourse Analysis (DDA). It was designed to investigate the constitutive representations of oral-enunciative competence (OEC) in English constructed by some subjects when occupying distinct discursive places undergraduates (first synchrony) and graduates (second synchrony) majoring in Foreign Languages. Regarding the first synchrony (1997), I studied how eighteen (18) subjects represent their OEC in English and that of their classmates in the context of university conversation classes of English, how these representations are translated into their learning experiences and in which discursive formations (DFs) their discursive practices are circumscribed. With relation to the second synchrony (2005), I studied how eleven (11) of these same subjects represent their OEC in English and that of their interlocutors in the several contexts experienced after graduation, how these representations are translated into the English teaching experiences in the different educational contexts and in which DFs their discursive practices are circumscribed when answering the AREDA Questionnaire. A study of the existing relations between the two synchronies was also carried out. Some findings of the study indicate that, in the first synchrony, the participants relation concerning their OEC in English is ruled by three representations: i) the OEC in English as lack; ii) the OEC in English as projection; iii) the OEC in English as exclusion. Such representations are interpenetrated and interconstituted and the discursive practices are circumscribed in some DFs that I classified as: DF of Lack (Lack of Linguistic Accuracy, Lack of Pertaining and Lack of Identification), Projective-Attributive DF (by Difference, Subjective and Interpellant) and DF of Exclusion (by Difference, by Denegation and by Resistance). In the second synchrony, the participants relation concerning their OEC in English is ruled by four representations: i) the OEC in English as lack; ii) the OEC in English as projection; iii) the OEC in English as reference; iv) resisting to the lack of OEC in English. These representations are interpenetrated and interconstituted and the discursive practices are circumscribed in some DFs that I described as: DF of Lack (Remaining and Constitutive), Projective- Attributive DF (by Difference, Subjective and Interpellant), DF of Orality Supremacy (Legitimating Praxis and Practice) and Heterotopic DF (by Event and by Desire). The discursive formations, in both synchronies, are in constant alterity, are interpenetrated in the continuum of the subjects discursive inscription and, for this reason, it cannot be said that one overlaps the other. By examining the dialogical relations among the two synchronies DFs, it was possible to observe that they are established by: i) resonance; ii) consonance; iii) dissonance; iv) dissension. In the social formation from where they enunciate, in each synchrony, the participants construct representations about OEC in English in a way that they inscribe themselves in DFs that coexist by dialogical and polyphonic relations that reveal their polyphonic referentiality. This referentiality is constructed from the discursive places, from the subjectforms and from the social places they occupy. It is also constituted by the DFs in which their discursive practices are inscribed. Such DFs coexist circumscribed in dialogic-polyphonic relations that, in the meaning dispersion, are similar, close, repetitive, contradictory, depart, dislocated. The subjects, in the different discursive places occupied in the two synchronies are in constant and continuing interpellation. The resistance to OEC in English occurs through the discontinuity of the act of becoming subject to face this resistance and to inscribe in many and different places that support such a resistance. Thus, the discourse of OEC in English , in this thesis, constitutes an effect of discursive places dislocation undergraduates and graduates; learners and teachers; users of the language in the ethos of both synchronies that permitted the diachronic analysis. From the polyphonic referentiality and from the diachrony established between the two synchronies, it is possible to say that there is, consequently, a discourse of oral-enunciative competence in English and that this discourse is an effect of dislocation of the discursive places occupied by the participants in the ethos in which they enunciate their utterances